ANALISIS FRAMING PESAN MORAL DALAM FILM HAFALAN SHALAT DELISA - Melta jannatanissa boer (Laboratorium Ilmu Komunikasi, Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) Universitas Ha, 2016)
Abstract MELTA JANNATANISSA BOER (C1D1 12 001) AN ANALYSIS OF FRAMING TO MORALITY ORDER AT HAFALAN SHALAT DELISA FILM. (Under the supervision by Dr.H. La Ode Muh. Umran, M.Si as the first supervisor and Hasriani Amin S.Sos., M.Si as the second supervisor. The problem was to discuss of this research is how to moral order form at Hafalan Shalat Delisa film. The Purpose of this research is to know the morality order form which framed into Hafalan shalat Delisa film. The object of this research is The Film of Hafalan Shalat Delisa, the director is Sony Gaokasak, release in 2011, genre films religious drama. This research focused at sequences film with to observe each sequences from film was contain moral order at each of the film scene. The theory of this research used theory of social construction by Peter L. Berger and Thomas Luckman. In this theory tell about that the social process trough of act and their interaction, where is an individual to create by continuing of the reality which belonging and experienced together with subjectively. The methodology of this research used observation technique at Hafalan Shalat Delisa Film. And then the data to analyzed using framing analysis model Zhongdang Pan and Gerald M. Kosicki with focused four element of framing are syntax, scripts, thematic, and rhetoric. This methodology was to find each squences with contain of the element moral order film and then to presented by using four this framing element, and to know how to framed ways of moral order in the film. As a result of the research showed that moral aspect in Hafalan sholat Delisa to indicate a lot of things can be learned from happening occurred. The problem may not make a moral someone broken, how to manage of the living between social problem which occurred in a religion manner or social function in the society. Finally this film to inform that moral order to taken of useful. Keywords : Hafalan Shalat Delisa Film, Framing ,Syntax, Scripts, Thematic, And Rhetoric,